The effects of empowerment program on knowledge, awareness and behavior of household contact of tuberculosis, Wat Yansangwararam hospital - ถาพันธ์, นริศรา; ตันวัฒนกุล, วสุธร; กิจปรีดาบริสุทธิ์, บุญธรรม (Disease Control Journal, 2013)
This research was to study the result effects of empowerment program on knowledge, awareness and behavior of household contact of tuberculosis The subjects were household at Watyansangwararam hospital. 24 of 48 household contact of tuberculosis were simply Random Sampling into an experimental group and other 24 into a control group. The empowerment program, which was conducted to the experimental group over a period of four weeks, while the control group was normal information. Statistical analysis was performed compare result before and after received program within the group by Paired t-test, between experimental and control groups by Independent t-test. The results found that the scores on knowledge, awareness and behavior after the experiment were higher than those of before experimental period (t = 15.85, 15.64 and 8.96 respectively), and those of participants in the control group (t = 8.50, 4.76 and 3.73 respectively), (p<0.001). The efficiency of empowerment program were 2.45, 1.71 and 1.74 times that of the control group respectively. This program can be development to prevent of tuberculosis.